2018
DOI: 10.1101/277285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimentally Induced Metamorphosis in Axolotl (Ambystoma mexicanum) Under Constant Diet Restructures Microbiota Accompanied by Reduced Limb Regenerative Capacity

Abstract: 38Axolotl (Ambystoma mexicanum) is a critically endangered salamander species and a 39 model organism for regenerative and developmental biology. Despite life-long neoteny in 40 nature and in captive-bred colonies, metamorphosis of these animals can be 41 experimentally induced by administering Thyroid hormones (THs). However, biological 42 consequences of this experimental procedure, such as host microbiota response and 43 implications for regenerative capacity, remain largely unknown. Here, we systematically… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Similar to other studies of the gut microbiome across taxa, we found that both sex and body weight were important factors accounting for interindividual variation in community assemblage. However, further work is needed to identify the effect of metamorphic transition in cane toad gut microbiomes given that previous studies have shown that this is a factor regulating the composition of the microbiome in amphibians (Demircan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies of the gut microbiome across taxa, we found that both sex and body weight were important factors accounting for interindividual variation in community assemblage. However, further work is needed to identify the effect of metamorphic transition in cane toad gut microbiomes given that previous studies have shown that this is a factor regulating the composition of the microbiome in amphibians (Demircan et al, ).…”
Section: Discussionmentioning
confidence: 99%